Faktor-Faktor yang Mempengaruhi Kinerja Aparatur Pemerintah Daerah - Reisa Hesti Fani; Sri Rustiyaningsih; Dwi Handayani (Fakultas Bisnis, 2015)
The purpose of this research is to examine the budgetary participation, leadership style, organizational commitment and motivation to performance of the apparatus. There are many contradiction findings of earlier researchers. The object of this research is the head of department and heads of sub-section reports and programs in the Government of Madiun Residence. The data used research is primary data, data was collected by questionnaire. Multiple regression analysis is used to analysis hypothesis testing. The results are indicate that the budgetary participation has not signifikan effect to performance apparatus, while the leadership style, organizational commitment, and motivation significant positive effect on the performance of government apparatus.